The parent-of-origin lncRNA MISSEN regulates rice endosperm development - Yan-Fei Zhou (Nature Portfolio, 2021)
The cereal endosperm is a major determinant of seed size and shape. Here the authors show that a lncRNA, MISSEN, is expressed from the maternally derived allele in rice seeds and regulates a helicase family protein to support efficient nuclear division, distribution and cellularization in the endosperm.